The Effect of Company Image, Service Quality, and Completeness of Facilities on Customer Satisfaction In Bank Muamalat Rantau Prapat - Azmi Rizki Tanjung; Elida F S Simanjorang; Yudi Prayoga; Christine Herawati Limbong (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Research was conducted at PT Bank Muamalat KCP Rantaprapat. The objective of this research was to find out: To what extent is the influence of corporate image, service quality and completeness of facilities on customer satisfaction at PT Bank Muamalat KCP Rantauprapat.  The research subjects consisted of several customers, in this study the respondents were 100 people. Data collection techniques using questionnaires and observations. While the data analysis method used is the Research Instrument Test, Classical Assumption Test, Simultaneous Effect Significance Test (F), Partial Effect Significance Test (T Test), Determinant Coefficient (R2) using SPSS Statistics Version 22 software, then draw the appropriate conclusions. With research results. The results showed that the Company Image, Service Quality, and Completeness of Facilities Have a Positive Effect on Customer Satisfaction at PT Bank Muamalat KCP Rantauprapat, Keywords: Company Image, Service Quality, Facilities, Customer Satisfaction.